2017
DOI: 10.14740/jocmr2959w
|View full text |Cite
|
Sign up to set email alerts
|

C-Reactive Protein and Frailty in the Elderly: A Literature Review

Abstract: Chronic inflammation is a well-established background process in many age-related diseases. Many recent studies investigate the use of various inflammatory biomarkers such as C-reactive protein (CRP), interleukin-6, and interleukin-1 as predictors of physical and cognitive performance among elders. The phenotype of frailty has also been associated with underlying inflammatory mechanisms. The aim of this article was to review the literature referring to the correlation of CRP serum levels and frailty in older i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 41 publications
6
46
1
4
Order By: Relevance
“…. Furthermore, several studies support the direct association between serum CRP levels and frailty in elders [29]. In accordance, we found that elevated levels of CRP were associated with higher frailty scores in the study population.…”
Section: Discussionsupporting
confidence: 90%
“…. Furthermore, several studies support the direct association between serum CRP levels and frailty in elders [29]. In accordance, we found that elevated levels of CRP were associated with higher frailty scores in the study population.…”
Section: Discussionsupporting
confidence: 90%
“…For cross-sectional analyses, we did not wish to determine whether Wave 1 (age: 70 years) epigenetic data associated with Wave 2 (age: 73 years) phenotypic data in order to limit the potential issue of retrocausality. In this first section, we also investigated the cross-sectional association of an accelerated DNAm GrimAge with a number of physical (body mass index, height, grip strength, lung function and weight) and blood traits (albumin, C-reactive protein, cholesterol, creatinine, ferritin, interleukin-6 and iron; at Wave 2; age 73 years) that have been related to mortality and frailty in older age [34][35][36][37][38][39][40][41][42].…”
Section: Phenotypic Datamentioning
confidence: 99%
“…The major components of frailty leading to increased dysphagia are sarcopenia, functional impairment, and drugs affecting swallowing (58). Frailty is often associated with increased inflammation (59).…”
Section: The Frailty Phenotype and Dysphagiamentioning
confidence: 99%